Analisis Hubungan Penerapan Metode Game-Based Learning Berbantuan Wordwall Terhadap Motivasi Belajar Siswa SMK - Amelia W Pomolango; Frahmawati Bumulo; Imam Prawiranegara Gani; Ardiansyah Ardiansyah; Mamang Kasim (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aims to analyze the relationship between the implementation of Wordwall-assisted Game-Based Learning and the learning motivation of Grade XII students at SMK Negeri 1 Bulango Utara. Methods – This study employed a quantitative approach using a survey method. The population consisted of all 63 Grade XII students at SMK Negeri 1 Bulango Utara. Using purposive sampling, 54 students who met the research criteria were selected as the sample. Data were collected through a validated and reliable questionnaire based on Keller’s ARCS motivation model. Data were analyzed using simple linear regression. Findings – The findings indicate a positive and statistically significant relationship between the implementation of Wordwall-assisted Game-Based Learning and students’ learning motivation. The coefficient of determination (R² = 0.388) suggests that variations in learning motivation are associated with variations in students’ perceptions of the implementation of Wordwall-assisted Game-Based Learning within the regression model, while the remaining 61.2% may be related to other factors not examined in this study.Research Implications – The findings provide empirical support for the relevance of the ARCS motivation framework in digital learning environments, particularly regarding students’ attention, relevance, confidence, and satisfaction. Practically, the study suggests that interactive web-based learning platforms such as Wordwall may be considered as alternative instructional media to support student engagement. However, the study is limited to one vocational school and relies on self-report questionnaire data, which may restrict the generalizability of the findings and does not allow causal conclusions to be drawn.